Statistical considerations for the development of prescriptive fetal and newborn growth standards in the INTERGROWTH‐21st Project. Issue 9 (17th May 2013) - Altman, DG; Ohuma, EO; ,
Abstract : The INTERGROWTH‐21 st Project has in its mandate to develop prescriptive standards for fetal, neonatal and preterm post‐neonatal growth. The project comprises three components: the Fetal Growth Longitudinal Study (FGLS), the Preterm Postnatal Follow‐up Study (PPFS), and the Newborn Cross‐Sectional Study (NCSS). We consider here the statistical aspects of the three components as they relate to the construction of these standards, in particular the sample size, and outline the principles that will guide the planned main analyses.